Development and validation of a disease severity index for ataxia of Charlevoix-Saguenay. (15th October 2019) - Gagnon, Cynthia; Brais, Bernard; Lessard, Isabelle; Lavoie, Caroline; Côté, Isabelle; Mathieu, Jean
Abstract : Objective: To develop a disease-specific severity index for adults with autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) (DSI-ARSACS) that considers the 3 components (pyramidal, cerebellar, neuropathic) of the disease, and to document its content validity, internal consistency, and construct validity. Methods: The Beta DSI-ARSACS (17 items) was developed based on literature review and expert inputs and then administered to 26 participants. Items reduction was based on Cronbach α and desirable criteria. Performance measures were administered to assess the construct validity of the final version of the DSI-ARSACS. Results: The final DSI-ARSACS have 8 items that can be easily performed during usual medical follow-up. The mean score was 19.6 ± 8.1 (range 6.0–35.5) and the Cronbach α was 0.912. The DSI-ARSACS score increased with disease stage and age ( p ⩽ 0.001) and was closely correlated with other measures assessing similar construct (9-Hole Peg Test, 10-Meter Walk Test, Scale for the Assessment and Rating of Ataxia, Berg Balance Scale, Barthel Index) ( r s = 0.75–0.95, p < 0.01). A moderate but not significant correlation was found with the 6-Minute Walk test ( r s = −0.611, p = 0.108). Conclusions: The DSI-ARSACS is a valid measure of disease severity for the adult ARSACS population that is able to distinguish between patients with different clinical profiles. Further documentation of metrologic properties is necessary, but these first results are promising.